Acceptance of smallholders toward technology application in oil palm plantation / Nurain Zamrut - Zamrut, Nurain (Faculty of Plantation and Agrotechnology, 2019)
Oil palm plantation is one of the most important sectors that contribute to Malaysian GDP. In order to develop this sector, technology has become one of the main components to improve the productivity of palm oil. However, the application of technology in oil palm plantation has remain low as smallholders are still depends on manual tools. This study was carried out to examine the acceptance of smallholders toward technology application in oil palm plantation. There are four independent variables as factors influences acceptance of technology which are attitude, subjective norm, perceive behavioral and extension agent. This study was conducted at Kg Mawai, Kota Tinggi, Johor among 152 smallholder that chosen randomly to answer the questionnaire via face to face interview. Reliability test, correlation analysis and multiple regression analysis was used to analyze the gathered data. To indicate result that extension agent has a strong positive correlation (p=0.638) and attitude has a very weak positive correlation (p=0.098). Meanwhile, multiple regression analysis indicates that 58.2% of acceptance technology application was explained by independent variables and another 41.8% was explained by other factors. The most influence independent variable was extension agent with the highest β-value which is 0.664 and the lowest influence independent variable perceived behavioral control with the lowest β-value which is 0.024. In conclusion, technology application lead to higher productivity and high income achievement in order to get high yield and sustain oil palm production.